Dr. B.R. Ambedkar’s Views on Population, Birth Control and Reproductive Rights - Sangeetha R. Mane; Shaheen J. Danasur; Ravindra M. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Dr. Ambedkar’s visionary stance on women’s rights—including what we today understand as reproductive rights—is equally significant but often underexplored. Though the contemporary framework of “Reproductive Rights” was not articulated during Ambedkar’s lifetime, his work consistently emphasized the centrality of bodily autonomy, gender equality, and social reform as preconditions for genuine liberation. Reproductive Rights can be traced through his writings, speeches, and especially his legislative efforts. Poverty is the cause of overpopulation in our country, unfortunately, today also, it is highly impossible to uproot poverty without the aid of birth-control. As a champion of female health and birth control measures, Ambedkar enthusiastically asserted it is, therefore, established that there is no go without recourse to modern contraceptives. As an economist, our expectations increase on how Dr Ambedkar visualized the role of population control policy in the development of the country further maintaining the economic balance of the state. The aim of the paper is to throw light on Ambedkar’s views on reproductive rights, though expressed in the language of his time, align closely with modern principles of reproductive justice. His insistence on equality, autonomy, and dignity for all, especially for women at the intersection of caste and gender oppression, makes his thought highly relevant to ongoing debates about reproductive freedom in India. As we revisit his legacy, it becomes clear that Ambedkar not only envisioned political freedom but also a deeply personal, social freedom—one that included the right of every woman to control her own body and destiny.